Dynamic changes in physic-chemical properties and bacterial community during natural fermentation of tomatoes - ZHOU,Xiaoli (2022)
Abstract This study revealed for the first time the dynamic changes of bacterial community and physic-chemical properties in the process of tomatoes fermentation. In the early phase of fermentation, Proteobacteria and Firmicutes account for 86.04% and 9.97%, respectively. Then, Firmicutes replaced Proteobacteria to be the dominant phylum from day 10. Among then, Lactobacillus decreased from 20 to 30 days and then rapidly increased. The total sugar showed a gradual decreased while the nitrite content increased in the early phases. The total acid content increased from initial 0.6% to 2.03% on day 30, mainly including citric acid, malic acid and lactic acid. In the later stages, the number of microorganisms and bacterial community tended to be stable, along with the content of organic acids and nitrite. During fermentation, the physic-chemical parameters inevitably change, mainly due to microbial metabolism, affecting in turns the development of the micro-ecosystem. These results contribute to our knowledge about bacterial participation in the process of fermentation and will help improve the quality of fermented food and vegetables.